2019
DOI: 10.1371/journal.pone.0210194
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of MRI in the decision-making process before radical prostatectomy: Systematic review and meta-analysis

Abstract: ContextMagnetic resonance imaging (MRI) is currently the most accurate imaging modality to assess local prostate cancer stage. Despite a growing body of evidence, incorporation of MRI images into decision-making process concerning surgical template of radical prostatectomy, is complex and still poorly understood.ObjectiveWe sought to determine the value of MRI in preoperative planning before radical prostatectomy.Materials and methodsSystematic search through electronic PubMed, EMBASE, and Cochrane databases f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 40 publications
0
23
0
3
Order By: Relevance
“…Furthermore, they showed that the appropriateness of the surgical decision modification based on the MRI findings was 77%. 71 Similarly, Druskin et al 70 showed that the use of preoperative MRI in patients undergoing RP resulted in a 5.6% decrease in the PSM rate.…”
Section: Mrimentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, they showed that the appropriateness of the surgical decision modification based on the MRI findings was 77%. 71 Similarly, Druskin et al 70 showed that the use of preoperative MRI in patients undergoing RP resulted in a 5.6% decrease in the PSM rate.…”
Section: Mrimentioning
confidence: 97%
“…Several authors studied the clinical value of preoperative MRI on surgical planning and PSM rates showing that it may influence the surgical decision in 26% to 59% of patients. [65][66][67][68][69][70] Recently, Kozikowski et al 71 reported, in their systematic review and meta-analysis, that MRI modified the NVB dissection on 1 or both sides in 35% of patients, of which 63% performed a more aggressive resection of the bundle and 37% had more preservation of the bundle. Furthermore, they showed that the appropriateness of the surgical decision modification based on the MRI findings was 77%.…”
Section: Mrimentioning
confidence: 99%
“…In contrast, the results of the systematic review and meta-analysis showed that the preoperative MRI altered the initial surgical plane in only one-third cases, but increased with the increasing PCa risk category. Also, modification based on MRI did not affect the PSM rate [ 33 ].…”
Section: Recent Innovations In Ns-rarpmentioning
confidence: 99%
“…With the widespread use of advanced MRI techniques and robot-assisted laparoscopic prostatectomy (RALP), it has become possible to evaluate the involvement of these critical structures in the tumor prior to surgery and spare them to reduce the risk of complications and recovery time 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%